Memahami Situasi Al-Nuzul Dalam Konteks Al-Tafsir Al-Haraki Al-Qur'an: Satu Tinjauan Terhadap Surah Al-Fath - Hj. Mohd. Yusoff, Zulkifli (Jurnal Usuluddin, 1996)
This article deals with one of the important aspects at the handing down of the al-Qur'an. The aspect dealt with is da'wah. It discusses the atmosphere of al-Nuzul in the understanding of the al-Qur'an. Any relationship between da'wah and al-Qur'an will have no meaning without taking into account this aspect. Therefore, this article will try to examine in detail this aspect by using surah al-Fath as a model.